Comparison of two new educational techniques on knowledge of nurses about cerebrovascular accident nursing care in emergency department - Zahra Dehghan; Nasrollah Alimohammadi; Shahla Mohamadirizi (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: One of the important challenges faced by health-care system is to raise the level of knowledge of nurses about cerebrovascular accident (CVA) nursing care in the emergency department. Therefore, the aim of this study was comparison of two new educational techniques (noninteractive multimedia learning and workshop) on knowledge of nurses about CVA nursing care in the emergency department. MATERIALS AND METHODS: This experimental study was conducted with a two-group design. Sixty-four eligible nurses working in the emergency department in selected hospitals affiliated to Isfahan University of Medical Sciences, Isfahan, Iran, were selected as the study participants. Nurses were randomly assigned into two groups of noninteractive multimedia (n = 32) and workshop (n = 32) using random number table. The data-gathering tools including a demographic questionnaire (6 items) and knowledge questionnaire (24 items) were completed before and 2 weeks after the intervention in both the groups. Data were analyzed using SPSS 18 and descriptive (mean and standard deviation) and analytical statistics (ANOVA, independent t-test, and paired t-test). The level of statistical significance was P ≤ 0.05. RESULTS: The result shows that independent t-test showed that there was not a significant difference between the mean total scores of nurses' knowledge before intervention in the two groups (P > 0/05). Furthermore, the results of paired t-test showed a significant difference in the knowledge score 2 weeks after compared to before the education in both the groups (P < 0.005). In addition, the results of independent t-test showed a significant difference in the knowledge score 2 weeks after the intervention in the two groups (P < 0.005). The average knowledge score in the workshop group was significantly higher than in noninteractive multimedia learning group. CONCLUSION: According to the result, new educational techniques such as noninteractive multimedia learning and workshop could improve knowledge of nurses about CVA nursing care in the emergency department.